2020
DOI: 10.31234/osf.io/qeap8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dual Evolutionary Foundations of Political Ideology Predict Divergent Responses to COVID-19

Abstract: A popular view, supported by several studies, is that liberals are more concerned than conservatives about COVID-19. This is puzzling given the strong pandemic responses from some conservative nations, and the well-established link between conservatism and threat-sensitivity. We argue a resolution is provided by the dual evolutionary foundations of political ideology, which track trade-offs between: (1) threat-driven group conformity (social conservatism or right-wing authoritarianism [RWA]) vs. individual aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 70 publications
(114 reference statements)
3
28
2
Order By: Relevance
“…This study advances prior research by investigating how four ideological factors–left-wing authoritarianism (LWA), right-wing authoritarianism (RWA), social dominance orientation (SDO), and libertarianism–shape attitudes toward COVID-19 vaccines and vaccine policies. Previous research has shown that ideological factors such as SDO and RWA predict COVID-19 risk perceptions, adherence to public health recommendations, and vaccine hesitancy ( Bilewicz & Soral, 2021 ; Choma, Hodson, Sumantry, Hanoch, & Gummerum, 2021 ; Fischer, Chaudhuri, & Atkinson, 2020 ). This research extends this line of scholarship and shows that ideologies also underscore the support for vaccine mandates and the punishment of unvaccinated individuals, which are heavily debated topics regarding the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…This study advances prior research by investigating how four ideological factors–left-wing authoritarianism (LWA), right-wing authoritarianism (RWA), social dominance orientation (SDO), and libertarianism–shape attitudes toward COVID-19 vaccines and vaccine policies. Previous research has shown that ideological factors such as SDO and RWA predict COVID-19 risk perceptions, adherence to public health recommendations, and vaccine hesitancy ( Bilewicz & Soral, 2021 ; Choma, Hodson, Sumantry, Hanoch, & Gummerum, 2021 ; Fischer, Chaudhuri, & Atkinson, 2020 ). This research extends this line of scholarship and shows that ideologies also underscore the support for vaccine mandates and the punishment of unvaccinated individuals, which are heavily debated topics regarding the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Poland ( Golec de Zavala et al, 2020 ) found small increases ( d av around 0.15) in right-wing authoritarianism (conformity) and sexual prejudice (conformity), and no changes in social-dominance orientation (cooperation) or political conservatism (ambiguous). A study in the United Kingdom ( Fischer et al, 2020 ) found a very small increase ( d av around 0.05) in right-wing authoritarianism (conformity) and no change in social-dominance orientation (cooperation). The increase in right-wing authoritarianism was only very weakly related to the perceived threat from the pandemic (explaining only 5% of the variance) and not related to actual exposure.…”
Section: Discussionmentioning
confidence: 98%
“…Note that although no prior experimental or longitudinal work has examined the effect of disease threat on moral foundations, there are several such studies of how various related constructs (e.g., social conservatism, political conservatism, right-wing authoritarianism, social-dominance orientation, gender stereotypes, and sexual prejudice) were affected by the COVID-19 pandemic ( Fischer et al, 2020 ; Golec de Zavala et al, 2020 ; Karwowski et al, 2020 ; Rosenfeld and Tomiyama, 2021 ) and the 2014 Ebola outbreak in the United States ( Beall et al, 2016 ; Inbar et al, 2016 ; Schaller et al, 2017 ; Tiokhin and Hruschka, 2017 ). These studies have yielded a mix of small effects and null effects.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Poland found small increases in right-wing authoritarianism and sexual prejudice (d av around 0.15) and no changes in social-dominance orientation or political conservatism (Golec de Zavala et al, 2020). A study in the United Kingdom found a very small increase in right-wing authoritarianism (d av around 0.05) and no change in social-dominance orientation (Fischer et al, 2020). Moreover, the increase in right-wing authoritarianism was only very weakly related to the perceived threat from the pandemic (explaining only 5 percent of the variance) and not related to actual exposure.…”
Section: Comparison To Other Studies Of the Covid-19 Pandemicmentioning
confidence: 99%